Global Islam and Political Patronage: Examining the Rise of Muslim Politics in Cambodia - Hasram, Khaidir (Universitas Islam Internasional Indonesia (UIII), 2023)
This article seeks to study Muslim political activism in Cambodia, a predominantly Buddhist-Monarch state in mainland Southeast Asia that is often considered a semi-authoritarian regime. Cambodia’s Muslim community constitutes a minority. However, they have actively participated in formal politics, aligning themselves with both the ruling and opposition parties. This engagement has culminated in several Muslim individuals sit in political positions within the government. Additionally, high-ranking Muslims have cultivated close ties with government authorities and the monarchy. This article is grounded in fieldwork conducted during 2017-2018, complemented by up-to-date information obtained from desk research and online interviews with research subjects. This article argues that the current wave of Muslim political activism in Cambodia can be seen as a continuation of the historical patron-client relationship between Muslims and local rulers. In contemporary times, this relationship has evolved, manifesting as patterns of clientelism, with Muslims positioned within the political framework of Cambodia’s ruling party. In this context, Muslims receive protection and are ensured access to political participation. Moreover, this article emphasises the role of connections to the global Muslim world as a significant political asset, enabling Cambodian Muslims to exert a considerable influence on the nation's political landscape.